Dinamika Kearifan Lokal Perkotaan: Solidaritas dan Toleransi Sosial di Tanjung Redeb - Muhammad Arya Dwiki Ressa Adriani (Yayasan Literasi Sains Indonesia, 2026)
Urbanization reshapes not only the physical landscape but also social relations, value systems, and everyday social ethics. In Indonesia, urbanization in small towns often occurs gradually, producing distinctive dynamics in the transformation of local wisdom. This article analyzes how urban local wisdom shapes and sustains social solidarity and social tolerance in Tanjung Redeb as a developing small town. This study adopts a qualitative literature review with thematic analysis of relevant journal articles and academic books addressing local wisdom, social solidarity, social tolerance, and urbanization dynamics. The synthesis identifies key patterns and conceptual relations explaining the transformation of local values in developing urban contexts. The findings show that local wisdom in Tanjung Redeb does not decline linearly due to urbanization but transforms into an adaptive system of social ethics embedded in everyday practices. Local wisdom functions as an ethical reference that strengthens social solidarity and facilitates tolerance in a plural society. Small towns thus operate as transitional social spaces where value negotiation occurs between communitarian relations and modern urban complexity. Theoretically, this article proposes the concept of Adaptive Local Wisdom, highlighting the continuity of local values through transformed social practices under gradual urbanization.